Personal exposure to PM2.5 in Chinese rural households in the Yangtze River Delta. (12th February 2019) - Hu, Ruolan; Wang, Shuxiao; Aunan, Kristin; Zhao, Minjiang; Chen, Lu; Liu, Zhaohui; Hansen, Mette H.
Abstract: High levels of PM2.5 exposure and associated health risks are of great concern in rural China. For this study, we used portable PM2.5 monitors for monitoring concentrations online, recorded personal time‐activity patterns, and analyzed the contribution from different microenvironments in rural areas of the Yangtze River Delta, China. The daily exposure levels of rural participants were 66 μg/m 3 (SD 40) in winter and 65 μg/m 3 (SD 16) in summer. Indoor exposure levels were usually higher than outdoor levels. The exposure levels during cooking in rural kitchens were 140 μg/m 3 (SD 116) in winter and 121 μg/m 3 (SD 70) in summer, the highest in all microenvironments. Winter and summer values were 252 μg/m 3 (SD 103) and 204 μg/m 3 (SD 105), respectively, for rural people using biomass for fuel, much higher than those for rural people using LPG and electricity. By combining PM2.5 concentrations and time spent in different microenvironments, we found that 92% (winter) and 85% (summer) of personal exposure to PM2.5 in rural areas was attributable to indoor microenvironments, of which kitchens accounted for 24% and 27%, respectively. Consequently, more effective policies and measures are needed to replace biomass fuel with LPG or electricity, which would benefit the health of the rural population in China.